Dampak Perjanjian 1752 Terhadap Konflik Keraton Kasepuhan Abad XVIII - Tendi, Tendi; Febrianto, Alfian (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The crux of the matter can be found in the guidelines for the succession of power in the Kasepuhan Cirebon Palace. Each party adheres to the conviction that the procedures they espouse are the authentic guidelines. Notably, relevant experts have not corroborated the veracity of all claims. Furthermore, there is a lack of reliable historical sources about the succession procedures within the Kasepuhan Cirebon Palace family. This lack of evidence renders the arguments of those seeking to resolve the issue even more tenuous. Because of the aforementioned considerations, the author endeavors to look at historical primary sources in the form of archives of agreements between the sultans of Cirebon in the past, stored by the National Archives of the Republic of Indonesia. It is hoped that the results of this study will serve as a scientific and academic reference for related parties, thereby facilitating the immediate resolution of the conflict that has arisen in the Kasepuhan Cirebon Palace.